A Novel Assay for Detection of Methicillin-Resistant Staphylococcus aureus Directly From Clinical Samples - McClure, Jo-Ann; Conly, John M.; Obasuyi, Osahon; Ward, Linda; Ugarte-Torres, Alejandra; Louie, Thomas; Zhang, Kunyan (Frontiers in Microbiology, 2020)
The timely detection of Methicillin-resistant Staphylococcus aureus (MRSA) is crucial for antimicrobial therapy and a key factor to limit the hospital spread of MRSA. Currently available commercial MRSA detection assays target the 3’ end of the orfX gene and the right extremity of Staphylococcal Cassette Chromosome mec (SCCmec). These assays suffer from both false positive due to SCC-like elements that lack mecA and false negative results due to the inability to detect new or variant SCCmec cassettes with the existing primers. We developed a novel MRSA detection scheme, designed to circumvent issues present in the existing commercial assays. Our assay demonstrated specificity and accuracy, capable of detecting prototypic strains of SCCmec types I-XIII [C(t) values ranged 8.58-26.29]. Previous false positive isolates (N=19) by Xpert MRSA nasal assay were accurately classified with our assay. Further validation with 218 randomly selected clinical isolates (73 MRSA, 75 MSSA, 43 MR-CoNS, and 27 MS-CoNS) confirmed its feasibility and practicality. Testing assay performance with 88 direct clinical swabs from 33 patients showed that the assay was 96.6% in agreement with clinical culture results. Our novel MRSA detection assay targets both the S. aureus specific sequence and the mecA/mecC genes simultaneously to overcome the false positive and false negative deficits of currently available commercial assays. The results validate our assay and confirmed its feasibility and practicality. The assay is not affected by SCCmec types and only needs modification if new mec homologues emerge and establishes a new platform for other emerging SCCmec types.